Morphology, microstructure, and doping behaviour: A comparison between different deposition methods for poly‐Si/SiOx passivating contacts. (4th March 2021) - Truong, Thien N.; Yan, Di; Nguyen, Cam‐Phu T.; Kho, Teng; Guthrey, Harvey; Seidel, Jan; Al‐Jassim, Mowafak; Cuevas, Andres; Macdonald, Daniel; Nguyen, Hieu T.
Abstract: Crystallographic structures, optoelectronic properties, and nanoscale surface morphologies of ex situ phosphorus‐doped polycrystalline silicon (poly‐Si)/SiO x passivating contacts, formed by different deposition methods (sputtering, plasma‐enhanced chemical vapour deposition [PECVD], and low‐pressure chemical vapour deposition [LPCVD]), are investigated and compared. Across all these deposition technologies, we noted the same trend: higher diffusion temperatures yield films that are more crystalline but that have rougher surface morphologies due to bigger surface crystal grains. Also, the recrystallization process of the as‐deposited Si films starts from the SiO x interface, rather than from the film surface and bulk. However, there are some distinct differences among these technologies. First, the LPCVD method yields the lowest deposition rate, roughest surfaces, and smallest degree of crystallinity on finished poly‐Si films. In contrast, the PECVD method has the highest deposition rate and smoothest surfaces for both as‐deposited Si and annealed poly‐Si films. Second, as‐deposited sputtered and PECVD Si films contain only an amorphous phase, whereas as‐deposited LPCVD films already has some crystalline phase. Third, the LPCVD phosphorus in‐diffusion into the substrate depends strongly on the initial film thickness, whereas for the other two methods, it is weakly dependent on thickness. Finally, the passivation quality of every poly‐Si film type has different responses to the film thickness and diffusion temperature, suggesting that the ex situ doping optimization should be performed independently. Abstract : Common methods to fabricate poly‐Si films are plasma‐enhanced chemical vapour deposition, low‐pressure chemical vapour deposition, and sputtering. Each resultant poly‐Si film has its unique characteristics. Herein, we investigate and compare the crystallographic structures, optoelectronic properties, and nanoscale morphologies of the ex situ phosphorus‐doped poly‐Si/SiO x passivating contacts formed by the different methods.